2021
DOI: 10.1038/s41467-021-24424-x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulate α-MnO2 nanofiber within graphene layer to tune surface electronic structure for efficient ozone decomposition

Abstract: Major challenges encountered when developing manganese-based materials for ozone decomposition are related to the low stability and water inactivation. To solve these problems, a hierarchical structure consisted of graphene encapsulating α-MnO2 nanofiber was developed. The optimized catalyst exhibited a stable ozone conversion efficiency of 80% and excellent stability over 100 h under a relative humidity (RH) of 20%. Even though the RH increased to 50%, the ozone conversion also reached 70%, well beyond the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 56 publications
3
78
0
Order By: Relevance
“…They found that α-MnO 2 performed the highest ozone removal efficiency. Zhu et al 203 developed a hierarchical structure consisted of graphene encapsulating α-MnO 2 nanofiber to address the challenges of the low stability and water inactivation during ozone decomposition. The optimized catalyst exhibited high ozone conversion efficiency of 80% and excellent stability over 100 h under a relative humidity (RH) of 20%.…”
Section: Application In Catalytic Oxidationmentioning
confidence: 99%
“…They found that α-MnO 2 performed the highest ozone removal efficiency. Zhu et al 203 developed a hierarchical structure consisted of graphene encapsulating α-MnO 2 nanofiber to address the challenges of the low stability and water inactivation during ozone decomposition. The optimized catalyst exhibited high ozone conversion efficiency of 80% and excellent stability over 100 h under a relative humidity (RH) of 20%.…”
Section: Application In Catalytic Oxidationmentioning
confidence: 99%
“…† Furthermore, the corresponding selected area electron diffraction patterns support the formation of the tetragonal structure of α-MnO 2 . 32,54,60,61 The planes (002), ( 200), ( 211), ( 220), (310), (400), (402), (411), ( 431), (440), (521), (541), (600), (602), (710), (730), and (741) are reported for α-MnO 2 (JCPDS no. 00-044-0141).…”
Section: Resultsmentioning
confidence: 99%
“…24 The peaks at 2θ = 13.461°, 20.874°, 28.829°, 37.507°, 62.818°, 69.688°, 77.101°, and 84.152°can be attributed to the Bragg diffractions caused by the (110), ( 200), (310), ( 211), ( 521), ( 541), ( 402) and (512) planes, respectively. 32,54,60 The XRD spectrum (Fig. 4E) and SAED pattern (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Development of new carbon material such as CNT, graphene oxide (GO) and reduced-GO (RGO) for new applications such as sensors, electronic devices, superconductors, catalysts, etc. have been widely investigated due to their high thermal and chemical stability, high aspect ratio and unique electronic properties, see studies by Zhang and Nicolosi [7], Szuromi [8], and Zhu et al, [9]. The fabrication methods used to form a film or layer on the glass or silicon substrate of these unique materials were chemical vapor deposition (CVD), spray coating, sputtering, or dipping techniques.…”
Section: Introductionmentioning
confidence: 99%